2018
DOI: 10.3775/jie.97.191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MgO Loading on the Production of Biodiesel from Jatropha Oil in the Presence of MgO/MCM-22 Catalyst

Abstract: This research focuses on the preparation, characterization and catalytic properties of novel magnesium oxide in mesoporous MCM-22 Silica (MgO/MCM-22) for biodiesel production from jatropha oil. The catalysts were prepared by impregnation method and characterized. Then, the catalyst were tested for biodiesel production from jatropha oil where the reaction parameters were studied. The obtained results of the characterization showed that, the prepared catalyst has an amorphous structure with high Si/Al ratio whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A stable catalyst retains its activity until the end of the reaction and after many times of recycling. [ 44 ] The recyclability of the MgO NPs catalyst was measured by the amount of methyl esters produced using the regenerated catalyst for repeated transesterification cycles. The methyl esters produced in every reaction were examined by gas chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…A stable catalyst retains its activity until the end of the reaction and after many times of recycling. [ 44 ] The recyclability of the MgO NPs catalyst was measured by the amount of methyl esters produced using the regenerated catalyst for repeated transesterification cycles. The methyl esters produced in every reaction were examined by gas chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…with an acid catalyst was achieved with the oil to methanol ratio of 1:10. In another work [23] transesterification of Jatropha oil was investigated using MgO/MCM-22 with different MgO loads as catalyst to evaluate the effect of MgO load, ratio of oil to methanol, reaction temperature, and reaction time. It was reported that the optimum conversion of 98 % was achieved using the catalyst with the MgO load of 20 %, with a ratio of oil to methanol of 1:15, reaction temperature of 70 C, reaction time of 100 min, with a 3 % amount of catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…One of the statistical methods that have been widely applied is known as Response Surface Methodology (RSM). This method has been applied to determine optimum conditions for transesterification of cooking oil [11,12], Jatropha oil [13,14], Jupati oil [4], rubber seed oil [15], palm oil [16,17] and soybean oil [9]. Recognizing the advantage offered by RSM, in present study this statistical method was applied to optimize transesterification of palm oil using zeolite-X as a catalyst.…”
Section: Introductionmentioning
confidence: 99%